PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) MATERI RELASI DAN FUNGSI PADA SISWA KELAS VIII SMPN 3 MAUPONGGO - Petronela Heriyana Putri; Stefanus Notan Tupen; Gregorius Taga (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2020)
This study aims to produce cooperative learning tools type Numbered Head Together (NHT) for Relationship and Function Material in class VIII students of SMPN 3 Mauponggo Satap 2019/2020 and to find out learning outcomes through the application of cooperative learning type of NHT, Relation and Function for students of SMPN 3 Satap Mauponggo. This research used in this research is experimental research. This study is the change that occurs between the pre-test and post-test values. Concomitant variable (Accompaniment): Student's pre-test score that must be reduced by covariance analysis. A sample is a portion (subsets) of a population. The sample in this study was 24 students of class VIII SMPN 3 Mauponggo Satap. The data analysis technique was obtained from the implementation stage using covariance analysis. Based on the results of the covariance analysis, it shows that F count = 67.35 is greater than F table = 4.28 with dk counting = 1 and dk denominator = 23 giving a significant value, indicating that cooperative learning type Numbered Head Together (NHT) is considered to improve learning outcomes for related material and functions class VIII students of SMPN 3 Satap Mauponggo 2019/2020.